Psychological well-being and healthy personality in sports practice - Vanesa García-Peñas; Olivia López Martínez; Enrique Garcés de Los Fayos Ruiz; Javier Corbalán Berná (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study investigates the relationship between sports practice, psychological well-being, and personality traits. It involved 761 participants from Spain (80.6%) and Argentina (19.4%), comprising 37.1% men and 62.9% women, with a mean age of 20.4 years (SD: 7.5). Among them, 70.8% engaged in regular sports activities, contrasting with 29.2% who did not. The Scales of Psychological Well-being and the NEO-FFI were the assessment instruments chosen in order to measure psychological well-being and personality traits. Data analysis consisted of Student's t-tests and multiple linear regression models. The results reveal higher scores in five of six psychological well-being dimensions and healthier personality traits among subjects that engage in sports practice. Noteworthy enhancements were found in Self-acceptance, Autonomy, Environmental Mastery, Personal Growth, and Life Purpose for sports participants. Personality traits significantly mediate between sports practice and psychological well-being dimensions. Extraversion, Openness, and Conscientiousness correlate positively with well-being dimensions, while Neuroticism negatively impacts several aspects.